Insights Into the Evolutionary History of the Subfamily Orthotrichoideae (Orthotrichaceae, Bryophyta): New and Former Supra-Specific Taxa So Far Obscured by Prevailing Homoplasy - Draper, Isabel; Garilleti, Ricardo; Calleja, Juan Antonio; Flagmeier, Maren; Mazimpaka, Vicente; Vigalondo, Beatriz; Lara, Francisco (Frontiers in Plant Science, 2021)
Mosses of the subfamily Orthotrichoideae represent one of the main components of the cryptogam epiphytic communities in temperate areas. During the last two decades, this taxonomical group has undergone an extensive revision that has led to its rearrangement at the generic level. However, their phylogenetic relationships and inferences on the evolutionary patterns that have driven the present diversity have little advanced. In this study, we present a dated molecular phylogenetic reconstruction at the subfamily level, including 130 samples that represent the 12 genera currently recognized within the subfamily, and the analysis of four molecular markers: ITS2, rps4, trnG, and trnL-F. We also analyze 13 morphological characters of systematic value to infer their origin and diagnostic utility within the subfamily. The phylogenetic reconstruction yields three main clades within the subfamily, two of which correspond to the tribe Zygodonteae, and one to Orthotricheae. Within Zygodonteae, the genus Zygodon results to be a polyphyletic artificial assembly, and we propose to separate a new genus named Australoria. Conversely, our results do not support the separation of Pentastichella and Pleurorthotrichum at the genus level and we therefore propose to include Pleurorthotrichum in Pentastichella. Regarding Orthotricheae, our analyses clearly allow the distinction of two subtribes: Orthotrichinae and Lewinskyinae. Within the latter, Ulota results a polyphyletic entity, and therefore we propose the segregation of a separate new genus named Atlantichella. Dating analyses allow us to conclude that the split of the tribes within Orthotrichoideae dates from the Middle Jurassic, while the diversification of Orthotrichum and Zygodon probably started during the Late Cretaceous. However, most of the extant genera of this subfamily seem to be younger, and apparently its highest diversification burst took place during the Oligocene. Finally, the analysis of the morphological traits reveals that most of the characters previously used to separate genera and here tested are homoplastic, which has hindered the taxonomical and systematic proposals for decades. However, even if there are not exclusive characters, all of the genera can be defined by the combination of a few characters.